KEPUTUSAN ORANG TUA DALAM MENGIJINKAN ANAK MENONTON FILM YANG MENGANDUNG UNSUR KEKERASAN - Refrida Chandra Wardani (Universitas Airlangga, 2018)
Superherofilm is a type of spectacle that is still widely consumed by children. Data from commonsense.org states that 68% of superhero films which aired in 2011-2016 have PG-13 ratings (Parental Strongly Cautioned) that contain violence and can have an impact on child development. Children who often watch television or movies tend to less concentration, less attention to the environment, and imitate what is shown. This study aimed to determine related factors of parental decisions in allowing children to watch violence films. This research was a quantitative with cross sectional approach. By using simple random sampling technique, the samples of this research taken as many as 93 parents of 3rd grade students at SDN Ketabang Surabaya. The data was collected by using questionnaire. This research used univariat and bivariate analysis. Most respondents are women (58.1%), age 28-45 years (79.6%), work as housewives (30.1%), and head of houshold have high income (68.8%). In relation to parental decisions in allowing children to watch violence films, most respondents have less knowledge (49.47%), less supportive attitude (84.94%), parents as personal reference in making decisions (68.82% ), unfulfilled facilities (52.69%), and high family culture (69.9%). Most respondents allow children to watch violence films (62.4%). The chisquare test showed that knowledge (p=0,000), availability of facilities (p=0,000), head of household income (p=0,000), and family culture (p = 0.002) are siginificantly related to parental decisions in allowing children to watch violence films. While the variables of attitude (p=0,096), personal references (p=0,249), and age (p=0,853) are not significantly related to parental decisions in allowing children to watch violence films. Keywords: children, parental decisions, superhero films, violence films